Metal surface structure nanocrystallization method based on in-situ shearing force

Through the nano-narrow method of metal surface structure based on in-situ shear force, combined with cold pressing, heating, pressurization, high-temperature and high-pressure torsion and high-temperature sintering, the problem of difficulty in preparing fully dense bulk metal materials with nano-level grains in the prior art is solved, the high density and nanostructure of the material are achieved, and the strength and toughness of the material are improved.

CN119549701AActive Publication Date: 2025-03-04AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411714941.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-04
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

It is difficult to prepare fully dense bulk metal materials with gradient structures in existing powder metallurgy technologies, and the grain size in the structure is difficult to reach the nanoscale.

Method used

The nanostructure of the metal surface structure based on in-situ shear force is adopted, and the density of the block is gradually improved and the formation of nanostructures is achieved by alternately laying the mixture of Ti powder, Al powder and WC powder and cold pressing, heating, pressurization, high-temperature and high-pressure torsion and high-temperature sintering.

Benefits of technology

A metal material with a density of 100% and nanostructure and multi-layer were successfully obtained, and the reinforced particles were dispersed in the microstructure, which improved the strength and toughness of the material, and the grain size in the tissue changed layer-like step-changing.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a metal surface structure nanocrystallization method based on in-situ shearing force, which comprises the following steps of: a, alternately laying a mixture of Ti powder, Al powder and WC powder in a mold, forming a laminated structure through cold pressing, and obtaining a block body with the density of 50-60% through cold pressing; b, the block obtained after cold pressing is heated and pressurized, the heating temperature ranges from 500 DEG C to 600 DEG C, and the density of the obtained block ranges from 70% to 80%; c, the heating and pressurizing state in the step b is kept, the temperature is increased to 800-900 DEG C, then the block is rotated, the rotating speed is 80-100 rad / min, the temperature is kept for 0.5-1 h, in the rotating process, WC powder particles serve as a grinding agent, adjacent Ti powder particles are crushed to be nanocrystallized, and the density of the finally obtained block is 90-95%; and d, finally, the block is subjected to high-temperature sintering, the heating temperature ranges from 1100 DEG C to 1200 DEG C, heat preservation is conducted for 0.5 h to 1 h, and after the block is cooled to the room temperature, the multi-layer metal material with the density of 100% and the nanometer structure is obtained. According to the method, due to interpenetration of the low-melting-point component and the high-melting-point component and maintenance of the reinforced particles in the morphology and position in the penetration process, the reinforced particles play a role in grinding the interior of the tissue in the high-pressure torsion process, and the reinforced particles are thoroughly fused into the tissue through high-temperature and high-pressure sintering after grinding, so that the high-temperature and high-pressure sintering effect is achieved. Therefore, the whole block structure is not easy to generate internal cracks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a metal surface nanostructure method based on in-situ shear force, belonging to the technical field of powder metallurgy. Background Art

[0002] The general solidification and forming methods of powder metallurgy block materials include hot isostatic pressing, hot pressing and sintering, and direct powder forging. Hot isostatic pressing and direct powder forging are suitable for the preparation of larger block materials, and the density of the block materials can reach 100%. Hot pressing and sintering are suitable for the preparation of smaller block materials, and the composition can be flexibly changed during the preparation process because it does not require prefabricated powder packaging. However, the structure is relatively coarse and no recrystallization occurs. Recrystallization relies on subsequent heat treatment, which increases the manufacturing cost.

[0003] The present invention is designed to address the above-mentioned existing technical situation and provides a method for metal surface nanostructure preparation based on in-situ shear force. Its purpose is to obtain a fully dense bulk metal material with a gradient structure. Reinforcing particles are dispersed in the structure of the metal material. The grain size on both sides of the reinforcing particles reaches the nanometer level, and the grain size in the structure shows a layered step change. This bulk metal material can be used in the preparation of components such as stepped shafts.

[0004] The objective of the present invention is achieved through the following technical solutions:

[0005] The steps of the metal surface nanostructure method based on in-situ shear force proposed by the present invention include:

[0006] a. A mixture of Ti powder, Al powder and WC powder is alternately layered in a mold and cold pressed to form a laminated structure. Each layer of Ti powder or a mixture of Al powder and WC powder is cold pressed on the entire block in the mold. The density of the block after cold pressing is 50-60%.

[0007] b. Heating and pressurizing the cold pressed block at a temperature of 500-600°C, at which the Al powder begins to soften, and the final block density is 70-80%;

[0008] c. Maintaining the heating and pressurizing state of step b and raising the temperature to 800-900°C, at which temperature the Al powder begins to melt and penetrate into the gaps between the Ti powder particles below, and then rotating the block at a speed of 80-100 rad / min for 0.5-1h. During the rotation, the WC powder particles act as a grinding agent and break the adjacent Ti powder particles into nano-sizes, and the final block density is 90-95%;

[0009] d. Finally, the block is subjected to high-temperature sintering at a heating temperature of 1100-1200°C for 0.5-1h, and then cooled to room temperature, to finally obtain a metal material with 100% density, nanostructure, and multiple layers.

[0010] In addition, in the above step a, the particle size of the Ti powder, Al powder and WC powder is -300 to -400 mesh, and the purity is 99.99%.

[0011] In addition, in the above step b, the Ti powder and Al powder particles in each layer of the block undergo plastic deformation, and the plastic deformation of the Ti powder and Al powder particles can buffer the WC powder particles and keep their initial morphology.

[0012] In addition, in the above step b, the thickness of the layer of the mixture of Al powder and WC powder is 70-80% of the thickness of the layer of Ti powder.

[0013] In addition, the pressures of the cold pressing in step a and the pressurizing in steps b and c are all 900 to 1000 MPa.

[0014] In addition, in the mixture of Al powder and WC powder, the volume fraction of Al powder is 60-70%.

[0015] In one embodiment, the steps of the metal surface nanostructure method based on in-situ shear force are as follows:

[0016] Step 1: Raw material preparation

[0017] Prepare Ti powder, Al powder and WC powder, the powder particle size is -300 to -400 mesh, and the purity is 99.99%;

[0018] Step 2: Powder cold pressing

[0019] In a vacuum environment, Ti powder is spread on the bottom of a cylindrical mold with a diameter of 100 to 200 mm, with a thickness of 1 to 3 mm, and then cold pressed at a pressure of 900 to 1000 MPa for 0.5 to 1 h to obtain a Ti powder layer, and then a mixture layer of Al powder and WC powder is spread on the cold pressed Ti powder layer, with a thickness of 70 to 80% of the thickness of the Ti powder layer, in which the volume fraction of Al powder is 60 to 70%, and then cold pressed again at a pressure of 900 to 1000 MPa for 0.5 to 1 h to obtain an Al powder and WC powder layer, wherein the Ti powder and the Al powder undergo plastic deformation, and under the buffering effect of the plastic deformation of the Ti powder and the Al powder, the WC powder maintains its initial morphology;

[0020] Step 3: Accumulated Cold Pressing

[0021] Repeat step 2 5 to 10 times until a Ti-Al / WC-Ti-Al / WC-…-Al / WC–Ti multilayer powder cold-pressed block is obtained, in which the Ti powder layer, Al powder and WC powder layer are mechanically bonded. From bottom to top, the density of the block gradually decreases as the plastic deformation of the Ti powder and Al powder gradually weakens. The density of the block after cold pressing is 50 to 60%.

[0022] Step 4: Heating and pressing

[0023] The cold pressed block is heated and pressurized at a temperature of 500-600°C. At this temperature, the Al powder begins to soften. Since the density of the block gradually decreases from bottom to top, the softened Al powder does not penetrate downward into the Ti powder layer. At the same time, the block is pressurized at a pressure of 900-1000 MPa for 0.5-1h. As the height of the block decreases, the density of the block tends to be uniform, the gas in the pores is discharged, and the combination of the Ti powder layer, the Al powder and the WC powder layer in the block is transformed into an adhesive combination. The final block density is 70-80%.

[0024] Step 5: High temperature and high pressure twisting

[0025] Keep the heating and pressurizing state of step 4 and raise the temperature to 800-900°C. At this temperature, the Al powder begins to melt and penetrate into the gaps between the Ti powder particles below. The WC powder particles, which have the same particle size as the Ti powder and the Al powder, remain between the Ti powder layer and the Al powder and the WC powder layer. Then rotate the block at a speed of 80-100 rad / min for 0.5-1h. During the rotation, the WC powder particles act as a grinding agent and break the adjacent Ti powder particles into nano-sizes. The final block density is 90-95%.

[0026] Step 6: High temperature sintering

[0027] Finally, the block is sintered at a high temperature of 1100-1200°C, kept warm for 0.5-1h, and then cooled to room temperature, ultimately obtaining a metal material with 100% density, nanostructure, and multiple layers.

[0028] The characteristics and beneficial effects of the technical solution of the present invention are:

[0029] 1. The scheme of the present invention provides a powder metallurgy method for obtaining nanostructures. This method is different from traditional methods such as hot isostatic pressing, hot pressing sintering and direct powder forging. It can be used to prepare large-scale block materials and flexibly change the block components. It does not require prefabricated powder packaging. The block structure is fine and fully dense, and nano-sized. The strengthening particles are dispersed in the microstructure.

[0030] Second, through the scheme of the present invention, different temperature rise treatments are the key to obtaining fully dense structures during the preparation process. Through the difference in melting points between the bulk components, the low melting point component undergoes plastic deformation-softening-melting and is fully combined with the high melting point component. Different from the interface reaction, this method is simpler and more efficient.

[0031] 3. Through the scheme of the present invention, due to the mutual penetration of low-melting point components and high-melting point components, and the maintenance of the morphology and position of the strengthening particles during the penetration process, the strengthening particles play a role of internal grinding of the organization during the high-pressure torsion process. The high-temperature and high-pressure sintering after grinding completely integrates the strengthening particles into the organization, making it difficult for the entire block organization to produce internal cracks. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be further described in detail below in conjunction with embodiments:

[0033] In this embodiment, the steps of the metal surface nanostructure method based on in-situ shear force of the present invention are as follows:

[0034] Step 1: Raw material preparation

[0035] Prepare Ti powder, Al powder and WC powder, the powder particle size is -300 to -400 mesh, and the purity is 99.99%;

[0036] Step 2: Powder cold pressing

[0037] In a vacuum environment, Ti powder is spread on the bottom of a cylindrical mold with a diameter of 100 to 200 mm, with a thickness of 1 to 3 mm, and then cold pressed at a pressure of 900 to 1000 MPa for 0.5 to 1 h to obtain a Ti powder layer, and then a mixture layer of Al powder and WC powder is spread on the cold pressed Ti powder layer, with a thickness of 70 to 80% of the thickness of the Ti powder layer, in which the volume fraction of Al powder is 60 to 70%, and then cold pressed again at a pressure of 900 to 1000 MPa for 0.5 to 1 h to obtain an Al powder and WC powder layer, wherein the Ti powder and the Al powder undergo plastic deformation, and under the buffering effect of the plastic deformation of the Ti powder and the Al powder, the WC powder maintains its initial morphology;

[0038] Step 3: Accumulated Cold Pressing

[0039] Repeat step 2 5 to 10 times until a Ti-Al / WC-Ti-Al / WC-…-Al / WC–Ti multilayer powder cold-pressed block is obtained, in which the Ti powder layer, Al powder and WC powder layer are mechanically bonded. From bottom to top, the density of the block gradually decreases as the plastic deformation of the Ti powder and Al powder gradually weakens. The density of the block after cold pressing is 50 to 60%.

[0040] Step 4: Heating and pressing

[0041] The cold pressed block is heated and pressurized at a temperature of 500-600°C. At this temperature, the Al powder begins to soften. Since the density of the block gradually decreases from bottom to top, the softened Al powder does not penetrate downward into the Ti powder layer. At the same time, the block is pressurized at a pressure of 900-1000 MPa for 0.5-1h. As the height of the block decreases, the density of the block tends to be uniform, the gas in the pores is discharged, and the combination of the Ti powder layer, the Al powder and the WC powder layer in the block is transformed into an adhesive combination. The final block density is 70-80%.

[0042] Step 5: High temperature and high pressure twisting

[0043] Keep the heating and pressurizing state of step 4 and raise the temperature to 800-900°C. At this temperature, the Al powder begins to melt and penetrate into the gaps between the Ti powder particles below. The WC powder particles, which have the same particle size as the Ti powder and the Al powder, remain between the Ti powder layer and the Al powder and the WC powder layer. Then rotate the block at a speed of 80-100 rad / min for 0.5-1h. During the rotation, the WC powder particles act as a grinding agent and break the adjacent Ti powder particles into nano-sizes. The final block density is 90-95%.

[0044] Step 6: High temperature sintering

[0045] Finally, the block is sintered at a high temperature of 1100-1200°C, kept warm for 0.5-1h, and then cooled to room temperature, ultimately obtaining a metal material with 100% density, nanostructure, and multiple layers.

Claims

1. A method for nano-structuring metal surface based on in-situ shear force, characterized in that: The steps of the method include: a. A mixture of Ti powder, Al powder and WC powder is alternately layered in a mold and cold pressed to form a laminated structure. Each layer of Ti powder or a mixture of Al powder and WC powder is cold pressed on the entire block in the mold. The density of the block after cold pressing is 50-60%. b. Heating and pressurizing the cold pressed block at a temperature of 500-600°C, at which the Al powder begins to soften, and the final block density is 70-80%; c. Maintaining the heating and pressurizing state of step b and raising the temperature to 800-900°C, at which temperature the Al powder begins to melt and penetrate into the gaps between the Ti powder particles below, and then rotating the block at a speed of 80-100 rad / min for 0.5-1h. During the rotation, the WC powder particles act as a grinding agent and break the adjacent Ti powder particles into nano-sizes, and the final block density is 90-95%; d. Finally, the block is subjected to high-temperature sintering at a heating temperature of 1100-1200°C for 0.5-1h, and then cooled to room temperature, to finally obtain a metal material with 100% density, nanostructure, and multiple layers.

2. The metal surface nanostructure method based on in-situ shear force according to claim 1, characterized in that: In the above step a, the particle size of the Ti powder, Al powder and WC powder is -300 to -400 mesh, and the purity is 99.99%.

3. The metal surface nanostructure method based on in-situ shear force according to claim 1, characterized in that: In the above step b, the Ti powder and Al powder particles in each layer of the block undergo plastic deformation, and the plastic deformation of the Ti powder and Al powder particles can buffer the WC powder particles and keep their initial morphology.

4. The metal surface nanostructure method based on in-situ shear force according to claim 1, characterized in that: In the above step b, the thickness of the layer of the mixture of Al powder and WC powder is 70-80% of the thickness of the layer of Ti powder.

5. The metal surface nanostructure method based on in-situ shear force according to claim 1, characterized in that: The pressures of the cold pressing in step a and the pressurizing in steps b and c are all 900-1000 MPa.

6. The metal surface nanostructure method based on in-situ shear force according to claim 1, characterized in that: In the mixture of Al powder and WC powder, the volume fraction of Al powder is 60-70%.

7. The metal surface nanostructure method based on in-situ shear force according to claim 1, characterized in that: The steps of this method are as follows: Step 1: Raw material preparation Prepare Ti powder, Al powder and WC powder, the powder particle size is -300 to -400 mesh, and the purity is 99.99%; Step 2: Powder cold pressing In a vacuum environment, Ti powder is spread on the bottom of a cylindrical mold with a diameter of 100 to 200 mm, with a thickness of 1 to 3 mm, and then cold pressed at a pressure of 900 to 1000 MPa for 0.5 to 1 h to obtain a Ti powder layer, and then a mixture layer of Al powder and WC powder is spread on the cold pressed Ti powder layer, with a thickness of 70 to 80% of the thickness of the Ti powder layer, in which the volume fraction of Al powder is 60 to 70%, and then cold pressed again at a pressure of 900 to 1000 MPa for 0.5 to 1 h to obtain an Al powder and WC powder layer, wherein the Ti powder and the Al powder undergo plastic deformation, and under the buffering effect of the plastic deformation of the Ti powder and the Al powder, the WC powder maintains its initial morphology; Step 3: Accumulated Cold Pressing Repeat step 2 5 to 10 times until a Ti-Al / WC-Ti-Al / WC-…-Al / WC–Ti multilayer powder cold-pressed block is obtained, in which the Ti powder layer, Al powder and WC powder layer are mechanically bonded. From bottom to top, the density of the block gradually decreases as the plastic deformation of the Ti powder and Al powder gradually weakens. The density of the block after cold pressing is 50 to 60%. Step 4: Heating and pressing The cold pressed block is heated and pressurized at a temperature of 500-600°C. At this temperature, the Al powder begins to soften. Since the density of the block gradually decreases from bottom to top, the softened Al powder does not penetrate downward into the Ti powder layer. At the same time, the block is pressurized at a pressure of 900-1000 MPa for 0.5-1h. As the height of the block decreases, the density of the block tends to be uniform, the gas in the pores is discharged, and the combination of the Ti powder layer, the Al powder and the WC powder layer in the block is transformed into an adhesive combination. The final block density is 70-80%. Step 5: High temperature and high pressure twisting Keep the heating and pressurizing state of step 4 and raise the temperature to 800-900°C. At this temperature, the Al powder begins to melt and penetrate into the gaps between the Ti powder particles below. The WC powder particles, which have the same particle size as the Ti powder and the Al powder, remain between the Ti powder layer and the Al powder and the WC powder layer. Then rotate the block at a speed of 80-100 rad / min for 0.5-1h. During the rotation, the WC powder particles act as a grinding agent and break the adjacent Ti powder particles into nano-sizes. The final block density is 90-95%. Step 6: High temperature sintering Finally, the block is sintered at a high temperature of 1100-1200°C, kept warm for 0.5-1h, and then cooled to room temperature, ultimately obtaining a metal material with 100% density, nanostructure, and multiple layers.

Citation Information

Patent Citations

  • Nanolizing method for metal surface

    CN101012493A

  • Preparation method of strengthened nano dispersion alloy

    CN110373565A

  • Powder bed material

    CN112055627A

  • Preparation method of high-quality anti-radiation tungsten alloy coating

    CN114921784A

  • Method for preparing and molding high-toughness beryllium / aluminum composite material through semi-solid plastic deformation

    CN115305375A